Asymmetric Organocatalytic Synthesis of aza‐Spirocyclic Compounds from Isothiocyanates and Isocyanides. Issue 16 (15th April 2021) - Laviós, Adrián; Sanz‐Marco, Amparo; Vila, Carlos; Blay, Gonzalo; Pedro, José R.
Abstract: The spirocyclic motif is present in natural products, chiral ligands, and compounds of pharmacological interest. Isothiocyanates as well as isocyanides bearing electron‐withdrawing groups in the α‐position can be deprotonated and react as formal dipoles on account of the presence of a nucleophilic carbanion and an electrophilic atom in the isothiocyanate or isocyanide functional groups. In the last years a number of procedures involving the formal [3+2] cycloaddition reaction of isothiocyanates or isocyanides with cyclic compounds bearing electrophilic exocyclic double bonds have been developed for the enantioselective synthesis of aza ‐spirocyclic compounds. Among them, organocatalysis has played a predominant role in the development of asymmetric versions for these reactions. The synthesis of spirooxindoles by using this methodology has received especial attention, although other spirocyclic scaffolds are available depending on the structure of the dipolarophiles and the formal isothiocyanate and isocyanide dipoles. Abstract : Formal [3+2] cycloaddition reactions of compounds bearing exocyclic unsaturated functional groups and isothiocyanate or isocyanide derivatives as formal 1, 3‐dipoles provide spirooxindoles and other aza ‐spirocyclic compounds. This review surveys the latest developments of these reactions under asymmetric organocatalysis.